The impact of alcoholic extract of Fenugreek and Nigella stiva on cholesterol and triglyceride values in healthy rabbits and with experimentally induced functional disorder of the liver (Journal of Hama University, 2022)
This research was conducted on( 60) male rabbits at the age( 6) months. The target of the research was to study the effect each of the alcohol extraction of fenugreek seeds and nigella stiva seeds on the level of cholesterol and triglycerides in rabbits that have dysfunction in liver activity. mediated by 4th Carbon Chloride. The population study were divided into(10) groups, the first group was coded as G1 (included 6 rabbits), and considered as control group, It had been provided with water and food only, the second group was included 6 rabbits and coded as G2 that was taken alcohol extraction of fenugreek with dose 500 mg /kg while G3 group was included 6 rabbits and taken alcohol extraction of fenugreek with dose 1000 mg/kg. The fourth group was coded as G4 and involved 6 rabbits that were taken alcohol extraction of Nigella Stiva with dose 200 mg./kg. The fifth group was coded as G5 and involved 6 rabbits that were taken alcohol extraction of Nigella Stiva with dose 300 mg./kg. The sixth group was coded as G6 and involved 6 rabbits that were taken dose as 1 ml/kg of live weight of 4th mix with oil pr Carbon Chloride twice weekly for 4 weeks. The seventh group was coded as G7 and involved 6 rabbits that were effected with disordered functional liver using 4th Carbon Chloride and taken alcohol extraction of fenugreek with dose 500 mg /kg. The eighth group was coded as G8 and involved 6 rabbits that were effected with disordered functional liver using 4th Carbon Chloride and taken alcohol extraction of fenugreek with dose 1000 mg /kg. The ninth group was coded as G9 and involved 6 rabbits that were effected with disordered functional liver using 4th Carbon Chloride 1m\kg and taken alcohol extraction of Nigella Stiva with dose 200 mg./kg. The tenth group was coded as G10 and involved 6 rabbits that were effected with disordered functional liver using 4th Carbon Chloride and taken alcohol extraction of Nigella Stiva with dose 300 mg./kg. Results showed that dealing of rabbits with both extractions given significant decrease in healthy rabbits weights (P≤0.05). As long as dealing with effected rabbits in functional disordered liver in both extractions leaded to significant decrease in effected rabbits via functional disordered liver compare to fourth effected group which none dealing with extractions.